A color in situ hybridization method with improved sensitivity for the detection of low-abundance mRNAs - Kovács, Beatrix; Gulya, Károly (Acta Biologica Szegediensis, 2001)
We have modified a nonradioactive (color) in situ hybridization method for the detection of mRNA populations, transcribed from the calmodulin (CaM) I gene, that exist in low abundances in tissues such as the white matter of the rat spinal cord. Our results indicate that increasing the pH of the hybridization solution from neutral to slightly alkaline (pH 8.0-8.5) drastically improves the detectable signal intensity of the digoxigenin-labeled CaM I gene-specific riboprobe while providing high spatial resolution. This method could be useful for the detection of other mRNA populations present in cells in low concentrations or in tissues where probe penetration might be impaired (e.g. a high lipid content).